2016
DOI: 10.4244/eijv12i6a117
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of bioresorbable vascular scaffolds following acute coronary syndrome is associated with reduced early neointimal growth and strut coverage

Abstract: Early neointimal growth and strut coverage are reduced following ACS in patients receiving BVS. These results may, in part, explain the high rates of ST in registry data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Differences in values observed between these two studies might derive from variety of measurement methodology used, from different time points of OCT examination but they might also suggest a diverse healing pattern of BVS in ACS and stable lesions. Data from histopathology and virtual histology intravascular ultrasound studies have shown that culprit lesions of ACS patients present more frequently as thin‐cup fibro‐atheromas, with greater amounts of necrotic core and smaller amounts of fibro‐fatty plaque compared to target lesions in SA patients . Shaw et al observed a correlation between the plaque composition and scaffold expansion and eccentricity immediately after BVS implantation .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in values observed between these two studies might derive from variety of measurement methodology used, from different time points of OCT examination but they might also suggest a diverse healing pattern of BVS in ACS and stable lesions. Data from histopathology and virtual histology intravascular ultrasound studies have shown that culprit lesions of ACS patients present more frequently as thin‐cup fibro‐atheromas, with greater amounts of necrotic core and smaller amounts of fibro‐fatty plaque compared to target lesions in SA patients . Shaw et al observed a correlation between the plaque composition and scaffold expansion and eccentricity immediately after BVS implantation .…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of a relatively small scaffold in a relatively larger vessel can result in incomplete apposition, predisposing to ST [35]. Higher rates of ST were also previously noted in patients with ACS which could be due to reduction of early neointimal growth and strut coverage [36,37]. Reasons for the increase in late ST in the Ca compared to the non Ca group include a role for technical factors such as suboptimal implantation with incomplete lesion coverage, underexpansion and malapposition [35,38] and possibly greater impact on the scaffold endothelization and resorption process from a reduced MLD in the Ca group.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the BP-DES platform appeared to outperform Xience when utilized for ST-segment elevation MI, a predefined subgroup analysis. Although the mechanisms for this remain unclear, patients presenting with an acute coronary syndrome may exhibit impaired strut endothelialization [48] and thus a more biocompatible polymer may better facilitate arterial healing. Real-world experience with the Orsiro platform is now also available from a 1356 patient registry, showing a TLF rate of 5.1% at 1 year [49].…”
Section: Orsiromentioning
confidence: 99%